Antibodies in melioidosis: the role of the indirect hemagglutination assay in evaluating patients and exposed populations - Chaichana, P; Jenjaroen, K; Amornchai, P; Chumseng, S; Langla, S; Rongkard, P; Sumonwiriya, M; Jeeyapant, A; Chantratita, N; Teparrukkul, P; Limmathurotsakul, D; Day, N; et al. (American Society of Tropical Medicine and Hygiene, 2018)
Melioidosis is a major neglected tropical disease with high mortality, caused by the Gram-negative bacterium Burkholderia pseudomallei (Bp). Microbiological culture remains the gold standard for diagnosis, but a simpler and more readily available test such as an antibody assay is highly desirable. In this study, we conducted a serological survey of blood donors (n = 1,060) and adult melioidosis patients (n = 200) in northeast Thailand to measure the antibody response to Bp using the indirect hemagglutination assay (IHA). We found that 38% of healthy adults (aged 17–59 years) have seropositivity (IHA titer ≥ 1:80). The seropositivity in healthy blood donors was associated with having a declared occupation of rice farmer and with residence in a nonurban area, but not with gender or age. In the melioidosis cohort, the seropositivity rate was higher in adult patients aged between 18 and 45 years (90%, 37/41) compared with those aged ≥ 45 years (68%, 108/159, P = 0.004). The seropositivity rate was significantly higher in people with diabetes (P = 0.008). Seropositivity was associated with decreased mortality on univariable analysis (P = 0.005), but not on multivariable analysis when adjusted for age, diabetes status, preexisting renal disease, and neutrophil count. This study confirms the presence of high background antibodies in an endemic region and demonstrates the limitations of using IHA during acute melioidosis in this population.